Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11187-016-9826-6
|View full text |Cite
|
Sign up to set email alerts
|

New players in entrepreneurial finance and why they are there

Abstract: The landscape for entrepreneurial finance has changed strongly over the last years. Many new players have entered the arena. This editorial introduces and describes the new players and compares them along the four dimensions: debt or equity, investment goal, investment approach, and investment target. Following this, we discuss the factors explaining the emergence of the new players and group them into supply-and demand-side factors. The editorial gives researchers and practitioners orientation about recent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
305
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(365 citation statements)
references
References 53 publications
(40 reference statements)
6
305
0
14
Order By: Relevance
“…Making the factors that contribute to the success and failure of ECF more salient not only benefits various investor types but also helps stabilize and establish a new market segment of entrepreneurial finance. In this way, our results more generally add to the recent literature in entrepreneurial finance (Block, Colombo, Cumming, & Vismara, ; Block, Fisch, & van Praag, ). Moreover, follow‐up funding and especially firm survival are important factors that help policy makers evaluate whether ECF is an efficient and worthwhile form of financing.…”
Section: Introductionsupporting
confidence: 86%
“…Making the factors that contribute to the success and failure of ECF more salient not only benefits various investor types but also helps stabilize and establish a new market segment of entrepreneurial finance. In this way, our results more generally add to the recent literature in entrepreneurial finance (Block, Colombo, Cumming, & Vismara, ; Block, Fisch, & van Praag, ). Moreover, follow‐up funding and especially firm survival are important factors that help policy makers evaluate whether ECF is an efficient and worthwhile form of financing.…”
Section: Introductionsupporting
confidence: 86%
“…In particular, we contribute to research on the selection criteria of early-stage investors looking at a new type of investor-the crowd. It has been found that specific information, such as education of the entrepreneurial team, protection of intellectual property rights, the venture's network, and firm alliances, are important drivers for the investment decisions of professional early-stage investors such as venture capital funds (Audretsch et al 2012;Baum and Silverman 2004;Block et al 2014Block et al , 2017aBusenitz et al 2005;Franke et al 2008;Jell et al 2011). It has also been shown that start-ups use this information to signal their value to investors (Audretsch et al 2012;Block et al 2014;Connelly et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, while traditional outside equity investors often rely on detailed due diligence to reduce adverse selection issues, equity crowdfunding relies on the wisdom of the crowd (Schwienbacher & Larralde, 2012). Moreover, while outside equity investors are often actively involved in their portfolio firms to reduce potential moral hazard issues and to add value, equity crowd investors are more passive within the firms they finance (Block, Colombo, et al, 2018). Still, equity crowd investors may provide valuable feedback and become brand ambassadors for the firm and its products (Schwienbacher & Larralde, 2012).…”
Section: Introductionmentioning
confidence: 99%